The good companions the complete series - Priestley, J. B. 1894-1984; Fanshawe, David 1942-2010 (Granada Ventures/Network, 2011)
"Charts the rollercoaster fortunes of a struggling concert party. Jess Oakroyd, discontented with his home, his work and his football team, tears up his Insurance Card and disappears into the night. He intends to go to Nuneaton, but instead finds himself on the ragged edges of show business sharing the trials and tribulations of the Good Companions as they tour seaside towns, industrial cities and rural backwaters in their search for success and stardom." [amazon.de]
Original: Großbritannien 1980-1981
Special features: "on the road": the making of the good companions (disc one)
Bildformat 1.33:1
Keywords: Film; DVD-Video